Community perspectives on the implementation of a group psychological intervention for adolescents with depression: A qualitative study in rural Nepal - Hassan, Eliz; BK, Prakash; Magar, Jananee; Luitel, Nagendra; Kohrt, Brandon A.; Jordans, Mark; Rose-Clarke, Kelly (Frontiers in Psychiatry, 2022)
Group-based psychological interventions could help to close the treatment gap for depression in low- resource settings, but implementation barriers exist. In Nepal we sought community members’ perspectives on how to implement group interpersonal therapy for adolescents. We conducted qualitative interviews with 25 adolescents with depression (aged 13-18) and seven health and Non-Governmental Organisation workers, and four focus groups with non-depressed adolescents, four with parents/guardians, and two with teachers (126 participants total). Data were analysed using the Framework Method. Participants recommended same-sex groups. School was the preferred location because it is accessible for adolescents and acceptable to parents. Adolescents wanted facilitators from their own community with good communication skills. They did not want parents or teachers to participate in groups but emphasised the need to inform parents and obtain their permission. Community members supported group psychological intervention. School-based psychological interventions facilitated by local people could be an acceptable option in rural Nepal.